The results of oceanographic researches in the coastal regions of Indian sector of Antarctica in December, 2011 and January-February, 2012 (by materials of 57th Russian Antarctic expedition) - Artamonov, A. Yu.; Artamonov, Yu. V.; Bochkarev, V. I.; Bunyakin, V. P.; Repina, I. A. (Ukrainian Antarctic Journal, 2013)
In the work the results of thermohaline water structure investigations in coastal regions of Indian sector of Antarctica, carrying out R/V “Academic Fedorov” in December, 2011 and January-February, 2012 are presented. Shown, that the intra-daily variability of temperature and salinity field is observed against a background of inter-daily changes, which due to displacement of boundary between cold and more fresh shelf water and more warm and salty ocean water. The water structure reconstruction is result from the active synoptic processes in atmosphere above Antarctic adjacent oceans areas.